The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-3083.2009.02278.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Platelets and Fresh Frozen Plasma in Contrast to Red Cell Concentrate on Unstimulated and Stimulated Cytokine Release in an In Vitro Model of Transfusion

Abstract: Transfusion of blood may contribute to immunomodulation. Leuco‐depleted standard blood products are supposed to result in less immunomodulation compared with whole blood. To determine the influence of leuco‐depleted blood products on the cytokine response, red blood cell concentrates (RBC), fresh frozen plasma (FFP) and platelet concentrates (PC) were investigated in an in vitro model of blood transfusion. Leuco‐depleted standard blood bank RBC, FFP and PC were mixed in vitro with AB0 compatible venous blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
4
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 31 publications
6
36
4
3
Order By: Relevance
“…In addition, in vitro allogeneic PRBC transfusion appears to have the potential to promote polymorphonuclear cell-mediated cytotoxicity and to suppress neutrophil locomotion (16) and apoptosis (17). Our findings of significant increases in proinflammatory cytokines after transfusion are in keeping with both in vitro evidence for induction of pro-and anti-inflammatory cytokines following PRBC exposure (18,19) and adult in vivo data (20). Specifically, PRBC transfusion has been demonstrated to result in significant increases in TNF-α (19) and IL-8 (21).…”
Section: Discussionsupporting
confidence: 77%
“…In addition, in vitro allogeneic PRBC transfusion appears to have the potential to promote polymorphonuclear cell-mediated cytotoxicity and to suppress neutrophil locomotion (16) and apoptosis (17). Our findings of significant increases in proinflammatory cytokines after transfusion are in keeping with both in vitro evidence for induction of pro-and anti-inflammatory cytokines following PRBC exposure (18,19) and adult in vivo data (20). Specifically, PRBC transfusion has been demonstrated to result in significant increases in TNF-α (19) and IL-8 (21).…”
Section: Discussionsupporting
confidence: 77%
“…An in-vitro study using a whole blood model reported increased interleukin (IL)-10 production and reduced tumour necrosis factor (TNF)-α production by the overall leukocytes in the culture supernatant following 24 h exposure to either autologous or allogeneic PRBC [81]. Similar studies consistently report suppression of TNF-α and augmentation of IL-10 responses following exposure to PRBC [89] or PRBC supernatants [85]. supernatants also augmented IL-6 production [85].…”
Section: In-vitro and In-vivo Models Of Prbc Transfusion (Related To mentioning
confidence: 90%
“…The potential for PRBC to modulate recipients' immune response and impact patient outcomes has been studied using in-vitro [79][80][81][82][83][84][85][86][87][88][89] and in-vivo [90] models. An in-vitro study using a whole blood model reported increased interleukin (IL)-10 production and reduced tumour necrosis factor (TNF)-α production by the overall leukocytes in the culture supernatant following 24 h exposure to either autologous or allogeneic PRBC [81].…”
Section: In-vitro and In-vivo Models Of Prbc Transfusion (Related To mentioning
confidence: 99%
See 2 more Smart Citations